Inequalities in Smoking and E-Cigarette Use in Young Adults With Mental Ill-Health, 20 years After Ireland's Smoking Ban - Joan Hanafin; Salome Sunday; Luke Clancy (SAGE Publishing, 2024)
Background: Ireland's Smoking Ban reduced health inequalities known to be associated with smoking but some groups may not have benefitted. Mental ill-health and smoking are known to be associated with health inequalities. Whether similar patterns exist for e-cigarette use is less clear, as few data exist. Objectives: To examine: (1) self-reported doctor-diagnosed mental ill-health in Irish 20-year-olds; (2) smoking, e-cigarette, and dual use in those with and without mental ill-health; and (3) protective and risk factors for smoking and e-cigarette use in these groups. Methods: We use cross-sectional data from 20 year-olds in Wave 4 of Growing Up in Ireland Child Cohort. They were asked to self-report mental ill-health which had been diagnosed by a clinician, and their smoking and e-cigarette use. All analyses were performed using SPSS v27. Results: 19.4% (n = 1008) of the total sample (n = 4729) reported a mental ill-health diagnosis. Comparing those with and without, those with mental ill-health had significantly higher prevalence of current smoking (47%, n = 419 vs 36%, n = 1361; OR 1.57, CI: 1.36, 1.82), e-cigarette use (17%, n = 152 vs 13%, n = 485; OR 1.40, CI:1.15, 1.70), and dual use (12%, n = 109 vs 9%, n = 328; OR 1.46, CI:1.16, 1.84). Risk factors for smoking and e-cigarette use were, earlier smoking initiation, peers or primary caregivers who smoked, being in paid employment, one-parent family background, and social media use. Being female was protective. Most risk factors were significantly higher in young adults with mental ill-health but, after adjusting for these variables, respondents with mental ill-health still have significantly higher adjusted higher odds of smoking (aOR 1.28, CI:1.05, 1.56). Conclusions: Inequalities in smoking and e-cigarette use in young adults with mental ill-health are evident 20 years after Ireland's National Smoking Ban. Despite extensive Tobacco Control interventions in the past 20 years, there is still need in Ireland for new targeted interventions to reduce health inequalities for left-behind young smokers with mental ill-health.